2017
DOI: 10.21608/scumj.2017.43562
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitamin D Levels in Women with Carpal Tunnel Syndrome

Abstract: Background: For decades, the role of vitamin D was limited to the formation and maintenance of bone as well as homeostasis of calcium and phosphate. Vitamin D is a steroid molecule, mainly synthesized in the skin from 7 dehydro cholesterol by ultraviolet irradiation or obtained through the diet. The major circulating metabolite of vitamin D is 25(OH) Vitamin D (25(OH)D), with a halflife of 21-30 days. Serum concentration of 25(OH) D is the most reliable biochemical index of vitamin status. Aim: The goal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[ 36 ] In their study on female patients with CTS, Okasha et al . [ 37 ] found that the level of Vitamin D in these patients was lower than normal. Similar results were also found by Gürsoy et al .…”
Section: Discussionmentioning
confidence: 97%
“…[ 36 ] In their study on female patients with CTS, Okasha et al . [ 37 ] found that the level of Vitamin D in these patients was lower than normal. Similar results were also found by Gürsoy et al .…”
Section: Discussionmentioning
confidence: 97%